Garantismo y publicismo en el proceso civil: un enfoque analítico - Cavani, Renzo (2021)
This essay uses an analytic methodology in order to differentiate three approaches in the classical debate between activist (publicist) and adversarial (guarantee) models in the continental tradition of civil procedural law: the historical, philosophical and institutional approach. It is showed that each one of them has different premises of discussion and also allows to reach particular consequences. We defend a proposal to distinguish between the activist model and the adversarial model from a philosophical point of view by identifying the political theory premises that are in their foundations. In the activist model, the State’s function is to be a provider for the protection of fundamental rights and, therefore, the judicial process is conceived as an instrument of the jurisdiction in order to achieve its public goals. On the other hand, in the adversarial model, the State’s function assumes an abstentionist- type in order to preserve fundamental rights and hence, far from being and nstrument of judicial power, the judicial process is conceived as a citizen’s guarantee oriented to control that very power.